ANALISIS IMPLEMENTASI PENYAJIAN LAPORAN KEUANGAN BERDASARKAN SAK EMKM PADA PT BINTANG WIJAYA ABADI BEKASI - Hj. Dewi Rejeki, SE., Ak., M.Ak. M.Si., CA. (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This research was conducted to determine the preparation of financial statements and whether the preparation of financial statements is in accordance with the SAK EMKM at PT Bintang Wijaya Abadi.The research method that will be used in this research is descriptive with a qualitative approach. This study uses primary data and secondary data. In addition, data is obtained through observation, interviews, and documentation. Financial report data taken from PT Bintang Wijaya Abadi in the form of daily cash reports, monthly bank statements, sales recapitulation and purchase recapitulation in 2017.The financial statements prepared by PT Bintang Wijaya Abadi are not in accordance with the SAK EMKM standar. The financial statements prepared by PT Bintang Wijaya Abadi only consist of the Daily Cash Report, Monthly Bank Reports, Sales Recapitulation and Purchase Recapitulation. The SAK EMKM states that the financial statements consist of the Financial Position Report, Income Statement and Notes to Financial Statements. In recognition, measurement and presentation by PT Bintang Wijaya Abadi is in accordance with SAK EMKM which uses an accrual basis